Analysis of Determinants of Carbon Fiber Strength: A Review - Salafuddin, Hafidz; Pranoto, Hadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2025)
In globalization and material advancement, carbon fiber has become a strategic solution in addressing sustainability challenges, especially in the automotive and aeronautical sectors, thanks to its superior lightweight and strength properties. This research aims to assess the various factors that influence the strength of carbon fibers and their potential integration in composites. The approach chosen is a literature review, which collects and synthesizes the results of recent studies to develop a thorough understanding of the strength and applications of carbon fibers. The findings of this study show significant improvements in tensile strength and weight reduction through the modification of carbon fiber with materials such as dopamine and its integration in aluminum matrix composites. Carbon fiber promises to be an important advance in developing composite materials that not only support sustainability but also adapt to the technical needs of contemporary industries. These results urge further research on efficient production methods to maximize the use of carbon fiber in wider applications.